2015
DOI: 10.1007/s11046-014-9857-y
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioides Species Determination: Does Sequence Analysis Agree with Restriction Fragment Length Polymorphism?

Abstract: Fifteen Coccidioides isolates were previously examined for genetic diversity using restriction fragment length polymorphism (RFLP); two fragment patterns were observed. Two isolates demonstrated one banding pattern (designated RFLP group I), while the remaining 13 isolates demonstrated a second pattern (designated RFLP group II). Recently, molecular studies supported the division of the genera Coccidioides into two species: Coccidioides posadasii and Coccidioides immitis. It has been assumed that the species d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…(Schröder et al 2016), Malassezia spp. (Wu et al 2015), Cryptococcus neoformans and C. gattii (Bovers et al 2006, 2008, Kwon-Chung & Varma 2006, Aminnejad et al 2012) and Coccidioides immitis and C. posadasii (Johnson et al 2015). However, to date, reports on these hybrids in filamentous fungi are restricted to the Neocosmospora solani complex (Short et al 2013, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…(Schröder et al 2016), Malassezia spp. (Wu et al 2015), Cryptococcus neoformans and C. gattii (Bovers et al 2006, 2008, Kwon-Chung & Varma 2006, Aminnejad et al 2012) and Coccidioides immitis and C. posadasii (Johnson et al 2015). However, to date, reports on these hybrids in filamentous fungi are restricted to the Neocosmospora solani complex (Short et al 2013, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although not being a dangerous disease in immunocompetent patients, it is estimated that 150 000 new cases of coccidioidomycosis occur annually in the USA, of which one‐third are fatal, being a special concern for immunocompromised persons (Odio et al, ). Genomic analyses of some populations from both species revealed the presence of a recent hybridization event (Neafsey et al, ), and more recently, the analysis of some genetic markers uncovered again the presence of hybrid organisms in these populations (Johnson et al, ). For instance, the genomic patterns of introgression between these two species revealed that at least 8% of the genes in C. immitis population may have been recently introgressed from C. posadasii , presenting an enrichment in genes associated with immune evasion and cell walls (Neafsey et al, ).…”
Section: Hybrids In Other Human Fungal Pathogensmentioning
confidence: 99%